Importance of spirometry, pulse oximetry and hematocrit in chronic obstructive pulmonary disease - A., Vinay Kumar; K., Sai Smarat; Reddy, Sony (International Journal of Advances in Medicine, 2019)
Background: To study the correlation of clinical features, spirometry, pulse oximetry assessment and haematocrit abnormalities in chronic obstructive pulmonary disease and to assess the severity of chronic obstructive pulmonary disease by spirometry. Methods: In the present study total 50 cases were selected on the basis of simple random sampling method from the Department of Pulmonary Medicine, Chalmeda Anand Rao Institute of Medical Sciences, Bommakal, Karimnagar, Telangana, India. During study period from June 2017 to December 2018. Results: About 50 patients of chronic obstructive pulmonary disease were studied. Majority of the patients were in the age group of 50-70 years. COPD was seen predominantly in male patients and majorities were smoker. In the majority of patients, the duration of illness was 6-10 years, cough with expectoration was present in all patients. As the number of cigarettes/day and duration increases the severity of the disease also increases in the studied population. In the study, about 40 % of cases were in stage III disease. Computerised spirometry was found to be most sensitive investigation in diagnosing and assessing the severity of the disease in all these cases. As the severity and duration of the disease increases, they are more prone to develop hypoxia and polycythaemia as a complication. In present study 8 patients had hypoxia, as assessed by pulse oximeter. Conclusions: Computerized spirometry is a very useful investigation in the management of chronic obstructive pulmonary disease. Pulse oximetry is a useful tool in diagnosing periods of oxygen desaturation. Pulse oximetry also useful in monitoring the oxygen therapy during management. Haematocrit analysis is a useful adjunct in assessing the severity of the disease. Polycythaemia, even though uncommon in chronic obstructive pulmonary disease patients is one of the rare but preventable complication with early cessation of smoking and with oxygen therapy.